Control interno y gestión de residuos sólidos en la Municipalidad Provincial de Ucayali 2025 - Vargas Quintana, Jesus Alberto (Universidad Nacional de la Amazonía Peruana, 2026)
The present analysis aimed to determine the relationship between internal control and solid waste management in the Provincial Municipality of Ucayali 2025. A basic approach was used, with a descriptive-correlational level and a non-experimental design. The population consisted of 48 workers, to whom the survey technique and a questionnaire were applied as a data collection instrument. The results showed that internal control in the MPU was rated as fair (44%), due to the fact that, on occasion, management and directive positions showed an active commitment to the implementation of the entity's internal control system. Regarding solid waste management, it was also considered fair (42%), since, on occasion, a periodic record of the volume of waste generated by the municipality was kept. Finally, it was determined that there was a positive and considerable relationship between internal control and solid waste management in the Provincial Municipality of Ucayali 2025, with a Pearson correlation coefficient of 0.694 and a bilateral significance value of 0.000.

El presente analisis tuvo como objetivo determinar la relación entre control interno y gestión de residuos sólidos en la Municipalidad Provincial de Ucayali 2025. Se empleó un enfoque básico, de nivel descriptivo-correlacional y diseño no experimental. La población estuvo conformada por 48 trabajadores, a quienes se aplicó la técnica de la encuesta y un cuestionario como instrumento de recolección de datos. Los resultados mostraron que el control interno en la MPU fue calificado como regular (44%), debido a que, en ocasiones, los cargos gerenciales y directivos mostraron un compromiso activo con la implementación del sistema de control interno de la entidad. En cuanto a la gestión de residuos sólidos, también se consideró regular (42%), ya que, en ocasiones, se llevaba un registro periódico del volumen de residuos generados por la municipalidad. Finalmente, se determinó que existió una relación positiva y considerable entre el control interno y la gestión de residuos sólidos en la Municipalidad Provincial de Ucayali 2025, con un coeficiente de correlación de Pearson de 0,694 y un valor de significancia bilateral de 0,000.
Keywords: Supervisión interna; Gestión ambiental; Residuos sólidos; Municipalidad; https://purl.org/pe-repo/ocde/ford#5.02.04